2023
DOI: 10.1177/17590914231181037
|View full text |Cite
|
Sign up to set email alerts
|

How Oxidative Stress Induces Depression?

Abstract: Depression increasingly affects a wide range and a large number of people worldwide, both physically and psychologically, which makes it a social problem requiring prompt attention and management. Accumulating clinical and animal studies have provided us with substantial insights of disease pathogenesis, especially central monoamine deficiency, which considerably promotes antidepressant research and clinical treatment. The first-line antidepressants mainly target the monoamine system, whose drawbacks mainly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 290 publications
0
7
0
Order By: Relevance
“…Furthermore, it has been demonstrated that antidepressants have antioxidant properties, and antioxidants exhibit antidepressant effects. For instance, fluoxetine and citalopram enhanced SOD activity and ascorbic acid levels, reducing malondialdehyde in MDD patients [21,29]. Research conducted on cell lines further supports the link between oxidative stress and depression.…”
Section: Oxidative Stress As a Key Contributor To Major Depressive Di...mentioning
confidence: 79%
See 3 more Smart Citations
“…Furthermore, it has been demonstrated that antidepressants have antioxidant properties, and antioxidants exhibit antidepressant effects. For instance, fluoxetine and citalopram enhanced SOD activity and ascorbic acid levels, reducing malondialdehyde in MDD patients [21,29]. Research conducted on cell lines further supports the link between oxidative stress and depression.…”
Section: Oxidative Stress As a Key Contributor To Major Depressive Di...mentioning
confidence: 79%
“…When combined with a decrease in antioxidant defenses, these mechanisms support the role of oxidative stress as a key player in depression [20]. Also, research reported elevated levels of peroxidation biomarkers combined with reduced antioxidant activity in the plasma and serum of individuals with MDD [21,24,25]. Targeting hypoxia-related pathways may also be a promising tool for depressive disorders in the context of mitigating high-oxidative stress levels, enhanced by hypoxia [8,26].…”
Section: Oxidative Stress As a Key Contributor To Major Depressive Di...mentioning
confidence: 85%
See 2 more Smart Citations
“…Signi cant attention has been paid to SO as it seems more harmful to health than obesity or sarcopenia alone [5]. Insulin resistance, in ammation, oxidative stress, and hormonal changes related to sarcopenia and obesity could be the pathogenesis of depression [6][7][8]. According to previous studies, obesity and sarcopenia alone were associated with depression.…”
Section: Introductionmentioning
confidence: 99%